Role of Social, Cultural and Economic Capitals in Perceived Quality of Life Among Old Age People in Kerala, India - Pradeep R Deshmukh; Amol R Dongre; KP Rajendran and Suresh Kumar (Indian Journal of Palliative Care, 2015)
Objective: To find out the relationship of collective social, economic, and cultural properties of a population on the perceived quality of life (QOL) among old age people. Materials and Methods: In a community‐based cross‐sectional study, we analyzed information on a representative sample of 900 old age (aged > 60 years) from 28 villages in Kollam district of Kerala. “ WHO‐Quality of Life ‐ BREF questionnaire” was used. Ethical clearance from Institutional Ethics Committee was obtained. The mean scores for “perceived” QOL for domains such as physical health, psychological health, social relations, and control of environments were calculated. The three scales (social capital, cultural capital, and economic capital) were standardized using z‐score transformation to make them comparable. Using multiple linear regression, we calculated the independent effect of economic capital, social capital, and cultural capital on perceived QOL among old people adjusted for age, sex, and the presence of chronic disease. Results: For overall QOL, only cultural capital contributed significantly. An increase of one unit z‐score cultural capital led to three units increase in overall QOL score (β = 3.362; 95% CI: 2.645-4.078). Social capital and cultural capital contributed significantly to the physical health domain of QOL. With one z‐score increase in social capital and cultural capital, QOL score of physical health domain increased by 0.2 units (β = 0. 227; 95% CI: 0.020-0.434), and 0.5 (β = 0. 596; 95% CI: 0.384-0.808) units, respectively. Psychological health domain and environmental domain were affected by all three capitals significantly. But, the social relations domain was significantly affected only by cultural capital (β = 0. 576; 95% CI: 0.373-0.779). Conclusion: Hence, the policies for old people should envision retaining our cultural and social norms along with the economic interventions for a better palliative care.